EFEKTIVITAS PENJARA TERHADAP PELAKU TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA - Dudi Haryadi (Scientia Regendi, 2020)
Imposition of Criminal Sanctions Prison against narcotics abuse principals is basically aimed at providing psychological or deterrent effects on narcotics users so that these users no longer use narcotics after completing the sentence handed down by the judge. In the Indonesian legal system before the imposition of criminal sanctions against narcotics abuse perpetrators by the Judge there are several stages that need to be carried out starting from the investigation, investigation, until the prosecution in the Court. The court has the authority to process any criminal case that takes place in its jurisdiction carried out by the judge through a trial. The problem in this paper is the extent to which the effectiveness of imprisonment sanctions against narcotics abuse offenders, as well as efforts to regulate imprisonment in suppressing drug dependence rates in the future. This study uses a sociological juridical approach. Primary data collection is carried out directly into the field by interviewing and studying case files that have to do with problems researched. Whereas secondary data was obtained through books, the Big Indonesian Dictionary, the Law Dictionary, Encyclopedias and other materials that are related to the writing of this thesis. Based on the results of the study it can be concluded that the effectiveness of the implementation of imprisonment can be viewed in terms of two main aspects of the purpose of punishment, namely aspects of community protection and aspects of improvement of the perpetrators of crime. Judges' considerations are the basis for imposing prison penal sanctions on narcotics offenders. Law No. 35/2009 concerning Narcotics regulates and recognizes special minimum provisions in imprisonment for narcotics abuse offenders.